Apatinib for recurrent/progressive glioblastoma multiforme: A salvage option - Zhang, Hong-Hong; Du, Xiao-Jing; Deng, Mei-Ling; Zheng, Lie; Yao, Dun-Chen; Wang, Zhi-Qiang; Yang, Qun-Ying; Wu, Shao-Xiong (Frontiers in Pharmacology, 2022)
Purpose: The recurrent/progressive glioblastoma multiforme (GBM) carries a dismal prognosis and the definitive treatment strategy has not yet been established. This study aimed to assess the efficacy and safety of apatinib in recurrent/progressive GBM patients. Materials and methods: The clinical data of 19 recurrent/progressive GBM patients who received apatinib treatment from November 2015 to December 2019 at Sun Yat-sen University Cancer Center were collected retrospectively in this study. Objective response rate (ORR), disease control rate (DCR), progression-free survival (PFS), overall survival (OS), and treatment-related adverse events (AEs) were reviewed and assessed. Results: The overall ORR was 52.6%, and the DCR was 73.7%. Median PFS and OS were 5.1 and 10.4 months, respectively. The 6-month PFS and OS rates were 38.9% and 68.4%, respectively. The 12-month PFS and OS rates were 16.7% and 36.8%, respectively. The treatment-related toxicities were generally well-tolerated. The most common grade 3/4 AEs were hand-foot syndrome (36.8%) and hypertension (21.1%). Conclusion: Our study showed that apatinib therapy provided a better salvaging option for recurrent/progressive GBM patients and the toxicity was manageable.